2019
DOI: 10.3390/md17120664
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Properties of Thiosilvatins

Abstract: The spread of studies on biodiversity in different environmental contexts is particularly fruitful for natural product discovery, with the finding of novel secondary metabolites and structural models, which are sometimes specific to certain organisms. Within the large class of the epipolythiodioxopiperazines, which are typical of fungi, thiosilvatins represent a homogeneous family that, so far, has been reported in low frequency in both marine and terrestrial contexts. However, recent observations indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In fact, the increasing number of studies on fungal genome sequences showed that the capability of fungi to produce secondary metabolites has been largely underestimated, because many of the fungal secondary metabolite biosynthetic gene clusters are silent under standard cultivation conditions. A large number of genes discovered by bioinformatic analyses based on polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes, putatively involved in secondary metabolites biosynthesis, are much higher than estimated, even in fungal species extensively studied for the production of secondary metabolites [ 125 , 126 ].…”
Section: Effect Of Growth Conditions On Low Molecular Weight Compomentioning
confidence: 99%
“…In fact, the increasing number of studies on fungal genome sequences showed that the capability of fungi to produce secondary metabolites has been largely underestimated, because many of the fungal secondary metabolite biosynthetic gene clusters are silent under standard cultivation conditions. A large number of genes discovered by bioinformatic analyses based on polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes, putatively involved in secondary metabolites biosynthesis, are much higher than estimated, even in fungal species extensively studied for the production of secondary metabolites [ 125 , 126 ].…”
Section: Effect Of Growth Conditions On Low Molecular Weight Compomentioning
confidence: 99%
“…The second purified product, cis-bis(methylthio)silvatin, is a member of thiosilvatins, a homogeneous family of compounds within the epipolythiodioxopiperazines, which, so far, have been reported from just 22 strains belonging to 17 fungal species from both marine and terrestrial sources. Half of these strains belong to Penicillium species, indicating that the genetic basis for thiosilvatin biosynthesis may be rooted in this genus [12]. Despite P. brevicompactum being very frequently recovered from many ecological contexts, this product has already been reported from just a single non-marine strain of this species, together with deprenyl-bis(methylthio)silvatin [18], indicative of either its infrequent occurrence or inherent difficulties in extraction and/or identification.…”
Section: Discussionmentioning
confidence: 99%
“…Our metabolomic analysis, carried out by combining several instrumental techniques and structural elucidation approaches, disclosed the ability by strain AN4 of P. brevicompactum to produce several compounds belonging to the thiosilvatin series [12], in evident connection with their biosynthetic relationships. Seven compounds in this series, of which five were not previously reported in P. brevicompactum, were detected as secondary metabolites of strain AN4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations